Affiliate Transactions and Conflicts of Interest (Legal Analysis of Transactions Between Pt. Telkomsel to The Company Pt. Karya Anak Bangsa) - Fadhel Hamzah, Muh (Universitas Sang Bumi Ruwa Jurai, 2024)
Affiliate transactions are any activities and/or transactions carried out by a public company or controlled company with affiliates of a public company or affiliates of members of the board of directors, members of the board of commissioners, major shareholders or controllers.The problem approach applied in this research is normative juridical, also known as doctrinal legal research. In this type of legal research, law is often conceptualized as what is written in statutory regulations (law in books) or law is conceptualized as rules or norms which are benchmarks for human behavior that is considered appropriate. Affiliate transactions and conflicts of interest (legal analysis of transactions between PT Telkomsel and GOTO), with allegations of Affiliate Transactions and Conflicts of Interest regarding PT Telkom's subsidiary, namely PT Telkomsel, to the company PT Karya Anak Bangsa or GOTO. The purpose of writing is none other than to find out and increase insight into the development of legal science, especially in the study of capital market and investment law, as well as to better understand and analyze how the financial services authority regulation No. 42 of 2020 concerning Affiliate Transactions and conflicts of interest